Prevalence of biological accidents due to accidental punction at the Universitary Hospital Virgen de la Victoria - Adolfo Romero Ruiz; Francisco Cabrera Cobos; Manuel Jiménez Ruiz; José Carlos Muñoz Pascual; Isabel Mª Ávila Rodríguez (Fundación para el Desarrollo de la Enfermería, 2007)
Nurses are the collective most affected by accidents derived from punctures. Consequently, it seems necessary to develop preventive strategies in order to decrease this problem. For that purpose, we have designed a research protocol in which we involved seven professionals from different areas of our hospital. We pretend to reach this goal within the following three years. The first step is to identify the real number of accidents in our own centre. We performed a retrospective exploratory study, gathering data from accidents declared from 2003 to 2005 at the University Hospital Virgen de la Victoria, describing the incidence of the different types of them and their distribution within professional categories. Then, we compared these data with those provided by the EPINETAC study (1996-2002). We concluded that, despite our hospital is not included in this multicenter study, our results are very similar, probably reflecting a homogenous distribution all over the country. The educational activities to be developed by our team must contribute to decrease this accident rates.